The Challenges Facing the Foreign Language Teacher Educator: A Proposed Teacher Education Model for EFL - Goldfus, Carol (Journal of NELTA, 2012)
As a result of the multi-cultural classroom in the 21st century, language teacher educators face new challenges; for example, young learners and those with language-based difficulties. In order to respond to these evolving needs, a new professional approach that combines theoretical knowledge with practical application is proposed. This approach targets what it is that teachers should know about literacy acquisition in at least two languages - a mother tongue and, in this case, English. The contribution of this proposed model to language education is to produce a teacher with declarative knowledge and research tools on the one hand, as well as the ability to cope with a heterogeneous classroom in a multicultural society on the other. This paper also intends to show how pre-service teacher education would benefit from an interdisciplinary approach with a combination of declarative knowledge and procedural knowledge with all teaching being ‘science-based practice’.DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6125 NELTA 2011; 16(1-2): 1-12